Use of Valproic acid and Cannabis sativa in the pharmacotherapeutic response to the treatment of epilepsy: a literature review (Research, Society and Development, 2022)
Objective: To compare the effectiveness of valproic acid and Cannabis sativa in the treatment of epilepsy through a literature review. Methods: it's about of a bibliographic review, exploratory and qualitative, carried out in the Google, Google Scholar, SCIELO - Scientific Electronic Library, Ministry of Health (MS) and Virtual Health Library databases, with a time frame from 2013 to 2022 , using the keywords: Epilepsy, Anticonvulsants, Valproic Acid, and Cannabis. Publications that did not have free access, duplicate works, that were not in accordance with the theme, and outside the period included in this research were excluded. Results: Valproic acid stands out among the most requested drugs to control seizures of various origins, as it is useful in controlling a wide range of clinical seizure disorders. However, the drugs used in the treatment are not effective in all patients, so the medicinal use of cannabidiol (CBD), a substance derived from Cannabis sativa, which finds barriers in its regulation in Brazil, however, presents many therapeutic benefits in the treatment of epileptic patients. Conclusion: When comparing Valproic acid (VPA) and Cannabis in the treatment of epilepsy, Cannabis stands out in its pharmacotherapeutic efficacy, as it allows the control of seizures and the side effects that valproic acid can cause. However, further pharmacokinetic studies of CBD are needed, so that its complete legalization in the country is carried out.